Effect of uncertainties in solar synoptic magnetic flux maps in modeling of solar wind. Issue 12 (15th December 2015) - Pevtsov, Alexei A.; Bertello, Luca; MacNeice, Peter
Abstract: Recently, the NSO/SOLIS team developed variance (error) maps that represent uncertainties in magnetic flux synoptic charts. These uncertainties are determined by the spatial variances of the magnetic flux distribution from full disk magnetograms that contribute to each bin in the synoptic chart. Here we present a study of the effects of variances on solar wind parameters (wind speed, density, magnetic field, and temperature) derived using the WSA–ENLIL model and ensemble modeling approach. We compare the results of the modeling with near-Earth solar wind magnetic field and plasma data as extracted from NASA/GSFC's OMNI data set. We show that analysis of uncertainties may be useful for understanding the sensitivity of the model predictions to short-term evolution of magnetic field and noise in the synoptic magnetograms.